DEVELOPING THE DIGITAL LEADERSHIP ISLAMIC GOVERNANCE INNOVATION MODEL: EVIDENCE FROM INDONESIA’S FIRST CYBER ISLAMIC UNIVERSITY - Moh Ali; Siti Maryam Munjiat; Anwar Sanusi; Taqiyuddin Taqiyuddin (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Digital transformation has reshaped governance in Islamic Higher Education Institutions (PTKI), yet limited research explains how Islamic leadership values drive digital governance innovation. This study investigates UIN Siber Syekh Nurjati Cirebon, Indonesia’s first cyber-based Islamic state university, as an intrinsic case study. The objectives are to: 1) analyze Islamic digital leadership characteristics and their governance implications; 2) identify governance innovations that strengthen Islamic academic culture; 3) examine implementation challenges and leadership responses; and 4) develop the Digital Leadership–Islamic Governance Innovation (DL-IGI) model. Data were obtained from 24 institutional documents and 32 peer-reviewed publications and analyzed using Miles and Huberman’s interactive model supported by NVivo 14. Findings reveal five core Islamic digital leadership competencies—amanah-based vision, musyawarah-driven decision-making, ta’awun collaboration, tarbiyah-oriented change management, and mas’uliyyah cyber stewardship—and six governance innovations strengthening tafaqquh fi al-din practices. The proposed DL-IGI model offers a four-stage framework for PTKI digital transformation grounded in Islamic governance principles. This study contributes a contextually grounded framework that operationalizes established Islamic governance values within digital governance systems an empirical contribution absent from prior PTKI digital transformation literature.